2019
DOI: 10.1029/2018ef001113
|View full text |Cite
|
Sign up to set email alerts
|

China's Urban Methane Emissions From Municipal Wastewater Treatment Plant

Abstract: The increased number and capacity of municipal wastewater treatment plants (WWTPs) in China has driven the emission of methane (CH 4). Few studies have focused on quantification of CH 4 emissions from municipal WWTPs of different cities and analysis of socioeconomic factors influencing the quantity of emissions. Here we estimated CH 4 emissions from WWTPs in China for 229 prefectural-level cities, based on data from 2,019 working municipal WWTPs. The results show the total CH 4 emissions to be 1,169.8 thousand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…Studies at a regional level are usually based on a mass balance approach derived from the 2006 IPCC Guidelines for National Greenhouse Gas Inventories (IPCC, 2006). Researchers have evaluated CH 4 emissions at the regional level (Du et al, 2018; Ma et al, 2015) and city level (Zhao et al, 2019), and these estimations showed similar results to total national emissions (Table 4). Zhao et al (2019) found that CH 4 emissions from municipal WWTPs for China's 229 prefectural‐level cities were over three times that of the municipal WWTPs in the United States in 2016.…”
Section: Wastewater Treatment Systemsmentioning
confidence: 80%
See 1 more Smart Citation
“…Studies at a regional level are usually based on a mass balance approach derived from the 2006 IPCC Guidelines for National Greenhouse Gas Inventories (IPCC, 2006). Researchers have evaluated CH 4 emissions at the regional level (Du et al, 2018; Ma et al, 2015) and city level (Zhao et al, 2019), and these estimations showed similar results to total national emissions (Table 4). Zhao et al (2019) found that CH 4 emissions from municipal WWTPs for China's 229 prefectural‐level cities were over three times that of the municipal WWTPs in the United States in 2016.…”
Section: Wastewater Treatment Systemsmentioning
confidence: 80%
“…Researchers have evaluated CH 4 emissions at the regional level (Du et al, 2018; Ma et al, 2015) and city level (Zhao et al, 2019), and these estimations showed similar results to total national emissions (Table 4). Zhao et al (2019) found that CH 4 emissions from municipal WWTPs for China's 229 prefectural‐level cities were over three times that of the municipal WWTPs in the United States in 2016. Although the IPCC approach has considerable uncertainty (Law et al, 2012), it is still a suitable way to quantify CH 4 of WWTPs at a regional level compared with the onsite monitoring approach (Zhao et al, 2019).…”
Section: Wastewater Treatment Systemsmentioning
confidence: 80%
“…Freshwater aquaculture areas are from Bureau of Fisheries China 33 . Activity data for waste water treatment plants are from Zhao et al 34 . Other activity data are from the National Bureau of Statistics of China 35 .…”
Section: Emissions and Their Trends For Major Source Sectorsmentioning
confidence: 99%
“…small, village or town-owned coal mines 16,34 . Our CMM prior inventory includes 11,000 operating coal mines in 2010/2011, of which about 4000 mines have been abandoned over 2010-2017 16 (Fig.…”
Section: Emissions and Their Trends For Major Source Sectorsmentioning
confidence: 99%
See 1 more Smart Citation